Human Rights and the Legal System: Bridging the Gap Between Law and Justice - Lumna Yumna (LAWYER: Jurnal Hukum, 2024)
This article explores the intricate relationship between human rights and the legal system, highlighting the discrepancies that often exist between codified laws and the lived realities of justice. While legal frameworks are designed to safeguard fundamental human rights, systemic inequalities, political influences, and institutional limitations can hinder their effective implementation. By examining historical developments, case studies, and international human rights instruments, this article underscores the need for a more inclusive and responsive legal system. The analysis also emphasizes the role of judicial independence, legal education, and civic engagement in bridging the gap between law and justice. Ultimately, the article advocates for a transformative approach to legal reform that prioritizes human dignity, equity, and accountability.